La policromia dei Monochromata La ricerca del colore su dipinti su lastre di marmo di età romana - Lenzi, Sara (Premio Ricerca «Città di Firenze», 2016)
The so-called "monochromes" on marble are twelve paintings on marble slabs from the Roman age, mostly coming from Herculaneum, and are now preserved at the National Archaeological Museum of Naples and at the Kunsthistorisches Museum of Vienna. These paintings were included in several publications. Despite that, they continued to raise many questions and there was a lack of studies focusing entirely on them. Furthermore, it had barely been clarified that, despite the name "monochromes", these works are completely polychrome. By combining the archaeological data and the information obtained from the non-invasive archaeometrical analysis, it was possible to achieve brand new results, which allowed for a better understanding of some aspects of these works, such as their iconography, the used pigments used and the clients' choices.